Automatic Supervisory System Synthesis for Port Cranes Collision Prevention by Using Petri Net - Danko Kezić (Promet (Zagreb), 2006)
The article deals with the system of port cranes comprisingtwo independently controlled cranes which are simultaneouslyengaged in the transhipment of cargo between a vessel and arailway wagon assembly alongside. The crane operator's errorcan lead to tlie collision of cranes. Therefore, it is necessary toinstall the supervisor in an automatic control system with thefunctions of continuous supervision of the process of cranemovement, and blocking of commands that can lead to collision.The article shows the method of crane system modellingas a discrete event system by using PIT and P-timed Petri nets.There is a proposal of a formal mathematic method for calculationof the state supervisor by P-invariant method. The supervisorcalculated in this way is maximally permissive supervisor.The efficiency of the supervisor is verified by a computer simulation.